Characterization of the Chloroplast Genome Facilitated the Transformation of Parachlorella kessleri-I, A Potential Marine Alga for Biofuel Production - Nawkarkar, Prachi; Chugh, Sagrika; Sharma, Surbhi; Jain, Mukesh; Kajla, Sachin; Kumar, Shashi (Current Genomics, 2020)
Introduction: The microalga Parachlorella kessleri-I produces high biomass and lipid content that could be suitable for producing economically viable biofuel at a commercial scale. Sequencing the complete chloroplast genome is crucial for the construction of a species-specific chloroplast transformation vector. Methods: In this study, the complete chloroplast genome sequence (cpDNA) of P. kessleri-I was assembled; annotated and genetic transformation of the chloroplast was optimized. For the chloroplast transformation, we have tested two antibiotic resistance makers, aminoglycoside adenine transferase (aadA) gene and Sh-ble gene conferring resistance to spectinomycin and zeocin, respectively. Transgene integration and homoplasty determination were confirmed using PCR, Southern blot and Droplet Digital PCR. Results: The chloroplast genome (109,642 bp) exhibited a quadripartite structure with two reverse repeat regions (IRA and IRB), a long single copy (LSC), and a small single copy (SSC) region. The genome encodes 116 genes, with 80 protein-coding genes, 32 tRNAs and 4 rRNAs. The cpDNA provided essential information like codons, UTRs and flank sequences for homologous recombination to make a species-specific vector that facilitated the transformation of P. kessleri-I chloroplast. The transgenic algal colonies were retrieved on a TAP medium containing 400 mg. L-1 spectinomycin, but no transgenic was recovered on the zeocin-supplemented medium. PCR and Southern blot analysis ascertained the transgene integration into the chloroplast genome, via homologous recombination. The chloroplast genome copy number in wildtype and transgenic P. kessleri-I was determined using Droplet Digital PCR. Conclusion: The optimization of stable chloroplast transformation in marine alga P. kessleri-I should open a gateway for directly engineering the strain for carbon concentration mechanisms to fix more CO2, improving the photosynthetic efficiency and reducing the overall biofuels production cost.
Keywords: genetic engineering